2014
DOI: 10.1371/journal.pone.0112452
|View full text |Cite
|
Sign up to set email alerts
|

Dental Status of New Caledonian Children: Is There a Need for a New Oral Health Promotion Programme?

Abstract: BackgroundBefore implementing a new oral health promotion program in the French overseas territory of Nouvelle Calédonie, the health authorities needed recent data about dental status of the New Caledonian child population.ObjectivesThis study aimed to describe the dental status of 6, 9 and 12-yr-old New Caledonian children and to investigate the environmental and behavioural risk factors related to oral health.MethodsA randomly selected sample of 2734 children (744 6-yr-olds, 789 9-yr-olds, and 1201 12-yr-old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

5
2

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 30 publications
1
22
0
2
Order By: Relevance
“…It has been recently reported that one in two 12-year-old children in New Caledonia (NC) was affected by dental caries with at least one untreated cavitated lesion [ 1 ]. As in other developed countries of the Pacific, socio-economic status and ethnicity had a strong influence on dental status leading to high oral health disparities [ 1 3 ]. Thus, implementing effective oral health promotion interventions is necessary in this overseas French territory, especially for children and adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…It has been recently reported that one in two 12-year-old children in New Caledonia (NC) was affected by dental caries with at least one untreated cavitated lesion [ 1 ]. As in other developed countries of the Pacific, socio-economic status and ethnicity had a strong influence on dental status leading to high oral health disparities [ 1 3 ]. Thus, implementing effective oral health promotion interventions is necessary in this overseas French territory, especially for children and adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Radiographs were not used. Six general dental practitioners performed the children's examinations, after having been calibrated through a training course described in a previous study [6]. The presence of dental sealants was recorded.…”
Section: Study Variablesmentioning
confidence: 99%
“…Caries experience was unevenly distributed in the population, with one third of 12-yr-olds having more than five untreated carious teeth. The number of carious lesions was related to their unfavourable lifestyle, deprived social status and lack of preventive dental care [6]. The prevalence of overweight and obesity was high and greatly increasing between the ages of 6 (respectively 10.8% and 7.8%) and 12 (respectively 22.2% and 20.5%), with one third of the 12-yr-olds having an excess of abdominal adiposity.…”
Section: Introductionmentioning
confidence: 99%
“…Radiographs were not used. Six general dental practitioners performed the children's examinations, after having been calibrated through a training course described in a previous study [4].…”
Section: Study Variablesmentioning
confidence: 99%
“…Caries experience was unevenly distributed in the population, with one third of 12-yr-olds having more than five untreated carious teeth. The number of carious lesions was related to the unfavourable lifestyle, deprived social status and no preventive dental care [4].…”
Section: Introductionmentioning
confidence: 99%